Transformation of the Urban Public Transport System in Kupang City - Yefry Cornianto ADOE; Ajis Salim Adang DJAHA; Hendrik TODA (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2025)
The purpose of this research is to analyze the condition of the existing urban transportation system in Kupang City, including its weaknesses, strengths, and development opportunities. It also identifies the main challenges faced in the process of transforming the urban transportation system. It also develops an urban transportation transformation strategy that aligns with the needs of the community and the conditions of Kupang City, to support sustainable mobility. The research used a qualitative approach, with informants selected purposively and actively. The results indicate that the urban transportation system in Kupang City is facing significant challenges in its transformation process. Although public transportation (angkot) remains available and operational, the dominance of online transportation services such as Grab and Maxim signals a shift in public preference toward more flexible, faster, and technology-based modes. The quality of conventional public transportation services remains low, with limitations in comfort, accessibility, and schedule certainty. Furthermore, the lack of regional regulations specifically governing the operation of urban transportation systems hinders efforts to reform and integrate transportation. Other challenges stem from the social and cultural aspects of the community's continued reliance on private vehicles, as well as the lack of institutional support and visionary public policies. The success of this transformation depends heavily on active collaboration between the government, transportation operators, and the community to create a modern, inclusive, and sustainable urban transportation system.